Pengkayaan Daphnia spp. Dengan Viterna Terhadap Kelangsungan Hidup Dan Pertumbuhan Larva Ikan Lele Dumbo (Clarias gariepinus) [Enrichment Of Daphnia spp. With Viterna To Survival And Growth Of African Catfish (Clarias gariepinus) Larvae] - Boedi Setya Rahardja; Woro Hastuti Satyantini; Naila Budiatin Wahyu Mufidah (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract African catfish (Clarias gariepinus) is one of fish consumption use to fulfill animal protein. The fulfillment need of animal protein with aquaculture effort, where as in the aquaculture effort will larvae quality increased. Increasingly of larvae quality with natural food had been adding feed supplement. Natural food to used is Daphnia spp. and then food supplement to used is viterna. The viterna will increase Daphnia nutritions, because of the viterna contains many nutritions to survival and growth of African catfish. The aim of this study was to know the influence of Daphnia spp. enrichment with viterna to survival and growth of African catfish (Clarias gariepinus) larvae. The rearing of larvae during 40 days. This study used Complete Random Design. The treatment were A (present Daphnia spp. without viterna), B (Daphnia spp. enrichment with viterna 10 ml/L dose), C (Daphnia spp. enrichment with viterna 10 ml/L dose), D (Daphnia spp. enrichment with viterna 10 ml/L dose), E (Daphnia spp. enrichment with viterna 10 ml/L dose) dan F (Daphnia spp. enrichment with viterna 10 ml/L dose), each treatment with 4 replications. The result show that viterna applications to Daphnia was significantly influenced (p<0,05) to survival African catfish larvae. The highest survival was E treatment (7,25 %). The viterna leaf to Daphnia spp. Was significantly influenced (p<0,05) to specific growth rate African catfish larvae. The highest specific growth rate was B treatment (1,885 %BW/day).